Analysis of The Implementation For Good Governance on The Development of Local Government in Makassar City - Muharram HAM, Mahar (Universitas Muhammadiyah Makassar, 2024)
The aim of this research is to analyze the Implementation of Good Governance to see the development and growth of the Makassar city regional government. This type of research uses qualitative research. The results of this research show that the development and growth of local government in the city of Makassar is based on the results of research and discussions. The implementation of the principles of Good Governance in the Makassar City Government has gone quite well, but is not yet optimal. The conclusion in this journal is that the principle of transparency, weakness of information management, government transparency, has not been well developed. Furthermore, the implementation of the principle of responsiveness of the authorities tends to be slow with the waiting time for dispute resolution being perceived to be long. The principle of public accountability really hopes that the form of accountability reports needs to be published through the media. And the author's suggestion is: In an effort to optimize the implementation of the principle of participation in the city government, it is necessary to carry out regular and programmed public debate activities every week down to the village level, and form advocacy institutions at the sub-district level. In an effort to optimize the implementation of transparency principles, city governments need to develop a government transparency management information system through e-government. And in an effort to optimize the implementation of the principle of responsiveness, it is necessary to form a Community Dispute Resolution Team.